'In the beginning was the word': the Society for Editors and Proofreaders 30th annual conference. (March 2020) - Kingdom, Ann
Abstract : Kingdom: The SfEP 30th annual conference Ann Kingdom reports on her experiences at the conference of the Society for Editors and Proofreaders, held at Aston University, Birmingham, from 14 to 16 September 2019.